Effect of Dietary Hemp Seed Cake on Systemic, Tissue and Organ Health of Commercial Laying Hens - Kasula, Rajasekhar; Solis , Fausto; Shaffer, Byron; Connett, Frank; Barrett, Chris; Cocker, Rodney; Willinghan, Eric (International Journal of Poultry Science, 2020)
Background and Objective: Although the inclusion of Hemp Seed Cake (HSC) in animal diets has shown benefits in animal performance, egg quality and human health, its inclusion in animal feed is still prohibited due to the potential residues of the of Δ-9 tetrahydrocannabinol, a psychoactive substance present in the hemp plant. Systemic and organ health are indicators of general health status of animals and any deviation from the expected parameters is an indication of the influence on health and safety of the nutrition provided to the animals, especially when a new ingredient is included in the ration. The objectives of this study were to determine the effect of HSC on systemic, tissue, organ, gut health and bone mineralization in commercial layer hens. Materials and Methods: Eight hundred (800) Bovan caged hens in lay at 30 weeks of age were distributed in 4 treatments of 200 hens per treatment based on inclusion levels of HSC, 0, 10, 20 and 30%. Each treatment comprised of 8 cages of 25 hens each that served as replicates. The observations per protocol were made over a period of 16 weeks following a 3 week acclimation. Results: The results of the study showed that feeding increasing levels of HSC up to 30% to commercial laying hens did not affect systemic parameters such as blood pH, blood profile, total protein and the mineral profiles; similarly, there was not effect on tissues and organ health parameters. A significant trend of reduction in moisture excretion over the control with HSC feeding was noted. The bone mineralization parameters were not significantly affected by the supplementation of HSC. Conclusion: The results of this trial confirm that feeding HSC up to 30% does not adversely affect the physiology of laying hens.